Are tumor-associated micro-angiogenesis and lymphangiogenesis considered as the novel prognostic factors for patients with Xp11.2 translocation renal cell carcinoma? - Wenliang Ma; Jun Yang; Ning Liu; Xiaohong Pu; Feng Qu; Linfeng Xu; Xiaozhi Zhao; Xiaogong Li; Gutian Zhang; Hongqian Guo; Dongmei Li; Weidong Gan (BMC Cancer, 2020)
Abstract Background Tumor micro-angiogenesis and lymphangiogenesis are effective prognostic predictors in many solid malignancies. However, its role on Xp11.2 translocation RCC has not been fully elucidated. Herein, we purposed to explore the correlation between quantitative parameters of tumor-related micro-angiogenesis or lymphangiogenesis and the prognosis of Xp11.2 translocation renal cell carcinoma (Xp11.2 translocation RCC). Methods Tissue samples were obtained from 34 Xp11.2 translocation RCC and 77 clear cell renal cell carcinoma (ccRCC) between January 2007 and December 2018. Micro-angiogenesis was detected using CD34 antibody and quantified with microvessel density (MVD) and microvessel area (MVA), while the lymphangiogenesis in RCC was immunostained with D2–40 antibody and assessed using lymphatic vessel density (LVD) and lymphatic vessel area (LVA). The Kaplan-Meier method of survival analysis was used to estimate prognosis, and both univariate and multivariate analysis was performing using the Cox proportional hazards. Results The MVD and MVA of Xp11.2 translocation RCC in two detected areas (intratumoral and peritumoral area) were not significantly different from that of ccRCC (all P > 0.05). Notably, D2–40-positive lymphatic vessels of Xp11.2 translocation RCC were highly detected in the peritumoral area compared to the intratumoral area. Interestingly, the peritumoral LVD and LVA of Xp11.2 translocation RCC were higher than that of ccRCC (all P < 0.05). Furthermore, both intratumoral MVD or MVA and peritumoral LVD or LVA were significantly associated with pT stage, pN stage, cM stage, AJCC stage, and WHO/ISUP grade (all P < 0.05). Univariate analysis of Cancer-specific survival (CSS) revealed that CSS was substantially longer in patients with low intratumoral MVD or MVA than in patients with high intratumoral MVD or MVA (P = 0.005 and P = 0.001, respectively). Lastly, the Cox proportional hazards model in CSS demonstrated that both intratumoral MVD or MVA and peritumoral LVD or LVA were not independent prognostic parameters (all P > 0.05). Conclusions This study outlines that Xp11.2 translocation RCC is a highly vascularized solid RCC, characterized by rich lymph vessels in the peritumoral area. Quantitative parameters of micro-angiogenesis and lymphangiogenesis could not be considered as novel prognostic factors for patients with xp11.2 translocation RCC.